METODE FUZZY MULTIPLE ATTRIBUTE DECISION MAKING (FMADM) SISTEM PENILAIAN CALON PENERIMA MANFAAT - Fatoni, Fatoni; Kurniawan, Kurniawan; Munandar, Wahid (Universitas Bina Darma, 2014)
Panti Sosial Bina Daksa Budi Perkasa Palembang, is one of the technical implementation unit of the Ministry of Social Affairs of the Republic Indonesia, which handles issues for persons with disabilities, the principal task of carrying out physical development, mental, social, vocational training, and re-socialization and further training. Beneficiary assessment system (client) used still manual. Yet there is a computerized system that was built specifically to manage the value of potential beneficiaries. It required a special system that can calculate the results of an assessment of the potential beneficiaries FMADM method. FMADM chosen method because this method determines the weight values for each attribute, followed by a ranking process that will select the best alternative from a number of alternatives. With this system can help section of the rehabilitation staff in selecting beneficiaries and help section chief in determining who the beneficiaries will get service restored.